Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines

The Logic of masculinist protection: Reflections on the current security state - Young, Iris Marion (Signs, 2003)
Keywords: amériques; approches et analyses; discipline; discours dominant; histoire et politique; masculinité; patriarcat; philosophie; philosophie politique; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; sécurité nationale; thématiques; états-unis

Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie